KEBIJAKAN PEMERINTAH DAN PARTISIPASI MASYARAKAT DALAM PEMBERDAYAAN MASYARAKAT DI DESA GIRILAYU - Hawa La'ala Nabilla Fada (ipdn, 2022)
The potential of Batik culture is used by the community and government in developing the economy by bringing batik productivity to the national and international realm. In an effort to realize this, a Community Empowerment was developed which functions to optimize the potential of batik to the maximum, there is a basis for community participation. In this study, researchers will explore policies regarding community empowerment in Girilayu Village. This policy relates to the efforts made by the village government in building a community empowerment by optimizing this potential. This study uses a qualitative research method with a case study approach. The data sources for this research were obtained from primary data sources, secondary data sources. Sampling technique is done by means of purposive sampling technique. The results of the study show that the village government started with the formation of 12 batik communities and was ratified through a decree. The relationship that was built with outside the region made Batik Girilayu known in the national arena so that Bank Indonesia chose it as a cluster of UMKM. With the assistance of Bank Indonesia, Batik Girilayu was provided with facilities, namely empowerment by planning empowerment and funding activities. Funding is also assisted by the DPR/DPRD who are interested in this empowerment. Empowerment activities have also reflected the approach to empowerment theory expressed by Edi Suharto, namely the 5 P (enabling, strengthening, protecting, supporting, and maintaining). Keywords: Batik, Empowerment, Government Policy, Community Participation